2021
DOI: 10.1002/ppsc.202000220
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Solvent on Dye‐Sensitized Solar Cell Efficiency: What is so Special About Acetonitrile?

Abstract: The selection of solvent for preparing a working electrode (and to act as the electrolyte) is known to influence the efficiency of dye‐sensitized solar cells. In this topical review, results taken from a systematic study are presented from the authors’ own lab examining how protic and aprotic solvents, as well as solvent polarity, affect adsorption of carboxylic dyes on the titanium dioxide nanoparticle surface and electron injection from the dye to the semiconductor. Adsorption of dye molecules on nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 116 publications
(201 reference statements)
0
10
0
Order By: Relevance
“…In our recent work, it was observed that flat Ag nanoplatelets acting as photosensitizers on TiO 2 nanorods (77% anatase phase, 23% rutile phase) exhibit enhanced photocatalytic efficiencies compared to spherical Ag nanoparticles . To understand the origin of this enhanced efficiency, TA spectroscopy (probed at 1900 cm –1 (0.24 eV), pumped at 400 nm (3.1 eV)) , was applied to investigate the electron dynamics in this nanocomposite . As depicted in Figure (inset), the rise of the TA signal, corresponding to the electron injection process, was fit to a single exponential rise function convoluted with the IRF (a Gaussian with a fwhm of 300 ± 10 fs). , The rise time was determined to be 13.1 ± 1.5 fs, which is comparable to the ∼15 fs previously measured for much smaller Ag nanoparticles by Lian and co-workers .…”
Section: Quantitative Modeling Of Electron Dynamicsmentioning
confidence: 99%
“…In our recent work, it was observed that flat Ag nanoplatelets acting as photosensitizers on TiO 2 nanorods (77% anatase phase, 23% rutile phase) exhibit enhanced photocatalytic efficiencies compared to spherical Ag nanoparticles . To understand the origin of this enhanced efficiency, TA spectroscopy (probed at 1900 cm –1 (0.24 eV), pumped at 400 nm (3.1 eV)) , was applied to investigate the electron dynamics in this nanocomposite . As depicted in Figure (inset), the rise of the TA signal, corresponding to the electron injection process, was fit to a single exponential rise function convoluted with the IRF (a Gaussian with a fwhm of 300 ± 10 fs). , The rise time was determined to be 13.1 ± 1.5 fs, which is comparable to the ∼15 fs previously measured for much smaller Ag nanoparticles by Lian and co-workers .…”
Section: Quantitative Modeling Of Electron Dynamicsmentioning
confidence: 99%
“…The dielectric constant values of solvents change the sensitizing ability of the dyes, which results in different aggregated structures and DSSC efficiencies. , A ruthenium-based N3 dye showed high J SC and low V OC values in acetonitrile and low J SC and high V OC values in a dimethyl sulfoxide sensitizing solvent, due to a change in the TiO 2 conduction band (CB) position and interfacial electron transfer from the dye to TiO 2 . A black dye showed significant changes in device efficiencies with a single solvent and with varying concentrations of two solvents . The Z907 dye showed different device efficiencies when the dye was sensitized into the two or more mixed solvents .…”
Section: Introductionmentioning
confidence: 99%
“…46 A black dye showed significant changes in device efficiencies with a single solvent and with varying concentrations of two solvents. 44 The Z907 dye showed different device efficiencies when the dye was sensitized into the two or more mixed solvents. 47 With changes in adsorption conditions by changing the sensitizing solvent to either single or mixed solvents and changing the adsorption time, porphyrin dyes showed changes in J SC , V OC , and device efficiencies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21,22] The prerequisites for glycerol conversion causes stability issues at the photoanode as the ubiquitously employed carboxylic acid-the best performing anchoring group for dyes to metal oxides-is prone to cleavage under aqueous alkaline conditions leading to dye desorption. [23,24] More importantly, the photovoltaic properties in aqueous dye-sensitized systems typically compare poorly with systems using an organic solvent like acetonitrile, [25] incurring losses in power conversion efficiency, lower injection efficiency and shifts of conduction band levels. [24] To make the DSPEC compatible with alkaline aqueous phase conditions required for glycerol oxidation, we envision a biphasic DSPEC system in which the photoanode is protected by an organic phase gel layer.…”
mentioning
confidence: 99%